Vitamin A Protects the Preterm Lamb Diaphragm Against Adverse Effects of Mechanical Ventilation - Song, Yong; Dahl, MarJanna; Leavitt, Wendy; Alvord, Jeremy; Bradford, Calan Y.; Albertine, Kurt H.; Pillow, J. Jane (Frontiers in Physiology, 2018)
Background: Preterm infants are deficient in vitamin A, which is essential for growth and development of the diaphragm. Preterm infants often require mechanical ventilation (MV) for respiratory distress. In adults, MV is associated with the development of ventilation-induced diaphragm dysfunction and difficulty weaning from the ventilator. We assessed the impact of MV on the preterm diaphragm and the protective effect of vitamin A during MV. Methods: Preterm lambs operatively delivered at ~131d gestation received respiratory support by synchronized intermittent mandatory ventilation for 3d. Lambs in the treated group received daily (24h) enteral doses of 2500 IU/kg/d vitamin A combined with 250 IU/kg/d retinoic acid (VARA) during MV, while MV control lambs were given saline. Unventilated fetal reference lambs were euthanized at birth, without being allowed to breathe. The fetal diaphragm was collected to quantify mRNA levels of myosin heavy chain (MHC) isoforms, atrophy genes, antioxidant genes, and pro-inflammatory genes; ubiquitin proteasome pathway activity; abundance of protein carbonyl, and protein abundance of metabolic signalling. Results: Postnatal MV significantly decreased MHC neonatal mRNA level but increased MHC IIx mRNA level (p<0.05). Proteasome activity increased after 3d MV, accompanied by increased MuRF1 mRNA level and accumulated protein carbonyl abundance. VARA supplementation decreased proteasome activity and FOXO1 signalling, down-regulated MuRF1 expression, and reduced reactive oxidant production. Conclusions: These findings suggest that 3d of MV results in abnormal myofibrillar composition, activation of the proteolytic pathway, and oxidative injury of diaphragms in mechanically ventilated preterm lambs. Daily enteral VARA protects the preterm diaphragm from these adverse effects.